Efektivitas Program Klaster Bank Indonesia Terhadap Peningkatan Pendapatan Petani Cabai Kelompok Juli Tani, Desa Sidodadi, Kecamatan Beringin, Kabupaten Deli Serdang - Rinaldi Simamora; Ahmad Rafiqi Tantawi; Mitra Musika Lubis (Jurnal Agriuma, 2021)
Juli Tani Group is a farmer group that received the cluster program from Bank Indonesia of Sumatera Utara for the red chili commodity. This study aims to determine the effectiveness of Bank Indonesia Cluster Program on the income level of chili farmers in the Juli Tani Group in Sidodadi Village, Beringin District, Deli Serdang Regency. The data used are primary data obtained directly from the sample of red chili farmers in Juli Tani Group using a questionnaire. Determination of the sample in this study using the Slovin method with a total sample of 52 respondents. Analysis of the data used in this research were (1) Analysis of the Effectiveness of the Cluster Program (2) Analysis of farm business income, to determine whether farming is profitable or not economically, the researcher uses Revenue Cost Ratio (R / C Ratio) then (3) uses non-statistical parametric with the Spearman Rank correlation test. Based on the research results, it was known that the Bank Indonesia cluster program is very effective in increasing the income of chili farmers in the Juli Tani Group in Sidodadi Village, Beringin District, Deli Serdang Regency with an average farmer income of Rp 117,404,895 per growing season.